'Everything is dimming out, little by little:' examining self-censorship among Venezuelan journalists. Issue 1 (2nd January 2021) - Pain, Paromita; Korin, Ezequiel
ABSTRACT: Using the conceptual frameworks of professional reflexivity and collective professional autonomy, our in-depth interviews with 25 journalists from Venezuela show that years of anti-press violence have ensured an atmosphere where journalists self-censor as the norm and where, through different forms, self-censorship has become a part of news routines. Journalists, especially those with over ten years of experience, clearly distinguished between self-censorship and other forms of suppression, but self-censorship has become so prevalent and infused in daily news routines, and so deeply internalised and reinforced that younger journalists and recent entrants into the profession consider self-censorship an integral part of their professional identity.